The Effectiveness of Weighted Blankets as a Sleep Promoting Behavior: A Quasi -Experimental Study - Amalia, Irish; Asih, Sali R; Wiswanti, Inge U; Saraswati, Ina (UI Scholars Hub, 2024)
Sleep is crucial to the overall well-being of individuals. Sleep deficiency can lead to various physical and mental health issues, including more severe insomnia, anxiety, and depressive symptoms. Improving sleep quality is often emphasized through sleep hygiene. An emerging nonpharmacological intervention is the use of weighted blankets, which apply deep-pressure stimulation to promote feelings of relaxation, comfort, and security similar to a gentle hug. This study explored the effects of weighted blankets on sleep quality and symptoms of insomnia, anxiety, and depression. Thirty participants (M = 33 years, SD = 9.13) used weighted blankets for 14 nights. They completed the Pittsburgh Sleep Quality Index (PSQI), Insomnia Severity Index (ISI), and Hopkins Symptom Checklist-25 items (HSCL-25) questionnaires. A wearable sleep tracker monitored physiological conditions such as resting heart rate, breathing quality, stress levels, total sleep duration, and deep sleep percentage. Results indicated significant improvements in subjective sleep quality and reductions in insomnia, anxiety, and depressive symptoms, although no significant changes were noted in objective sleep quality scores. As a quasi-experimental study with no control group, the study carries the limitations related to a quasi-design.